Evaluation of the Physicochemical and Biological Stability of Cetuximab under Various Stress Condition - Farjami, Afsaneh; Siahi-Shadbad, Mohammadreza; Akbarzadehlaleh, Parvin; Roshanzamir, Khashayar; Molavi, Ommoleila (Journal of Pharmacy & Pharmaceutical Sciences, 2019)
Cetuximab is a chimeric monoclonal antibody against epidermal growth factor receptor (EGFR) and it is approved for treatment of human colorectal cancer and squamous cell carcinoma of head and neck. The aim of this research was to study the stability of cetuximab finish product (5 mg/mL) under various stress conditions including mechanical, thermal, light stress, and various freeze-thaw cycles. To determine the effects of environmental stresses on the physicochemical properties and bioactivity of cetuximab, a combination of physicochemical and cell-based biological methods including size exclusion chromatography (SEC), cation exchange chromatography (CEX), flow cytometry-based binding assay, and MTS cell viability/proliferation assay was used. The results obtained by the SEC and CEX methods revealed that incubation of cetuximab at 25 and 30 °C, shaking, and various freeze-thaw cycles caused no physicochemical instability. However, functional analysis of the samples exposed to the above-mentioned conditions revealed a significant decrease in the bioactivity of cetuximab indicated by a significant reduction in the cell binding and growth inhibitory effects of cetuximab in EGFR overexpressing cancer cell line (A431). Incubation of cetuximab at 40 and 50 °C led to polymerization and fragmentation of the mAb and resulted in a significant decrease in the bioactivity of the mAb. Our findings show that the light exposure had the most destructive effects on physicochemical and biological characteristics of cetuximab. In conclusion, we found that all mentioned stress conditions significantly affect the bioactivity of cetuximab. Our finding highlights the importance of bioactivity evaluation of biopharmaceuticals in their quality control assessment.